ENGINEERING COMPARISON OF COMPOUNDS WITH NEW COUPLINGS WITH TAPERED CUFFS AND A TRADITIONAL CYLINDRICAL CONNECTION COUPLING FOR PE PIPES WITH NOMINAL DIAMETER OF 1000 MM - Robert Eckert (Advanced Engineering Research)
The concept of connecting large-diameter pipes by the electrofusion welding using couplings with tapered cuffs is considered. Practical aspects of the coupling of such pipes are described. In particular, the reasons for the increase in requirements to the quality of welded joints with the enlargement of the pipe diameter are stated. The design of the coupling with tapered cuffs, as well as the assembly technique of this type of coupling is considered. Two technologies – the electrofusion welding of large-diameter pipes using cylindrical couplings, and the electrofusion welding of pipes by means of couplings with tapered cuffs – are compared. In conclusion, a list of the European regulations on which the welds made by means of couplings with tapered cuffs are tested, is given.